Evaluating the effect of COVID-19 incidence on Emergency Departments admissions. Results from a retrospective study in Central Italy during the first year of pandemic - Quercioli, C.; Bosco, R.; Bova, G.; Mandò, M.; De Marco, M. F.; Dei, S.; Gusinu, R.; Messina, G. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Introduction. The COVID-19 pandemic has had a major impact on the Healthcare System, changing the patterns of Emergency Department access. In fact, accesses for trauma and less severe cases decreased significantly. This decline has generally been attributed to both the effects of the lockdown, imposed by the government, and the fear of being infected by SARS-CoV-2 in the hospital. However, the correlation between these elements is not yet clear, since the accesses to the Emergency Department did not increase either at the end of the lockdown or in the summer when the epidemiological situation was more favorable. Aim: To evaluate the association between trends of Emergency Department accesses and COVID-19 incidence in 2020. Methods. Data on Emergency Department accesses, by month and severity triage code, from 14 hospitals in southeastern Tuscany (Italy) were obtained from hospitals’ data warehouse. Official data on new cases of COVID-19 infection were used to calculate incidence. Hospitals were classified into 4 categories. Differences in Emergency Department access by month, triage code, and hospital type were investigated using Kruskal-Wallis analysis. Association between Emergency Department accesses and COVID-19 incidence was evaluated using a random-effect panel data analysis, adjusting for hospital type and triage code. Results. The trend of 268,072 Emergency Department accesses decreases substantially at the first pandemic peak; thereafter, it increased and decreased again until the minimum peak in November 2020. COVID-19 incidence appeared to be overlapping with an inverse direction. Monthly differences were significant (p<0.01) except for most severe codes. There was a significant inverse association between Emergency Department accesses and COVID-19 incidence (Coef. =-0.074, p<0.001) except for most severe cases (triage code 1: Coef. =-0.028, p=0.154). Conclusion. Emergency Department admissions trend followed the COVID-19 incidence, except for the most severe cases. Fear of infection seems to discourage patients from accessing Emergency Department for illnesses perceived as not serious.